Metal mixing in Minihalos: the descendants of pair-instability supernovae - Magg, Mattis; Schauer, Anna T. P.; Klessen, Ralf S.; Glover, Simon; Treß, Robin G.; Jaura, Ondrej (The astrophysical journal, 2022)
The lack of observations of abundance patterns originating in pair-instability supernovae has been a long-standing problem in relation to the first stars. This class of supernovae is expected to have an abundance pattern with a strong odd-even effect, making it substantially different from present-day supernovae. In this study, we use a cosmological radiation hydrodynamics simulation to model such supernovae and the subsequent formation of the second generation of stars. We incorporate streaming velocities for the first time. There are 14 star-forming minihalos in our 1 cMpc h −1 box, leading to 14 supernovae occurring before redshift z = 19.5, where we start reducing the complexity of the simulation. Following the explosions, extremely metal-poor stars form in 10 halos via internal and external enrichment, which makes it the most common outcome. Only one halo does not recollapse during the simulations. This result is at variance with the current (lack of) observations of metal-poor stars with pair-instability supernova abundance patterns, suggesting that these very massive stars might be rare even in the early universe. The results from this simulation also give us insights into what drives different modes of recollapse and what determines the mixing behavior of metals after very energetic supernovae.
Gesehen am 13.05.2022